An Overview and Management of Multiple Chronic Conditions - Akarsu, Sevgi (IntechOpen, 2020)
"Multiple chronic conditions," also known as multimorbidity, is a special situation frequently encountered by global healthcare professionals, especially internists/primary care physicians, neurologists, respiratory/pulmonologists, pain specialists, and oncologists, who spend more than three-quarters of their time in the treatment of chronic diseases and direct patient care. Thus, the increasing need for multidisciplinary approaches in the management of multiple chronic medical problems, rather than focusing on individual diseases, should be borne in mind by global healthcare professionals, public health professionals, healthcare providers, health policymakers, and pharmaceutical industries. This book is an up-to-date source of information for physicians, residents, and advanced medical students seeking a broader understanding of managing chronic disease clusters.